Investigating the Factors Associated with Increased Breast Cancer Incidence among Saudi Female Youth Aged 25-30 Years in the Absence of Family Medical History: A Cross-Sectional Study - Wejdan Khaled Alotaibi,; Mashael Ali Alahmari,; Majedah Salfiq Alanazi,; Nouf Saad Almutairi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Breast cancer rates are increasing among young Saudi Arabian women, even in the absence of a family history of the disease. This study aimed to identify risk factors associated with early onset breast cancer in this demographic. Methods: A case-control study was conducted with 500 Saudi women aged 25-30 diagnosed with breast cancer and 500 age-matched healthy controls. Data was collected via surveys on sociodemographic factors, lifestyle behaviors, reproductive history, and environmental exposures. Conditional logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: In multivariate analysis, significant risk factors for breast cancer included never breastfeeding (OR=2.61, 95%CI 1.83-3.72), oral contraceptive use >5 years (OR=1.89, 95%CI 1.37-2.61), smoking >5 pack-years (OR=2.14, 95%CI 1.44-3.17), obesity (OR=1.92, 95%CI 1.46-2.51), and working night shifts (OR=1.63, 95%CI 1.14-2.34). Higher education and vitamin D sufficiency were protective. Conclusions: Reproductive choices, lifestyle factors, and occupational exposures appear to influence breast cancer risk in young Saudi women. Public health efforts promoting breastfeeding, maintaining a healthy weight, avoiding long-term oral contraceptive use and smoking, and optimizing vitamin D levels may help reduce the burden of early onset breast cancer in this population. Workplace policies limiting night shift work for women may also be beneficial.